BINAR (BERBAGI, INOVASI, NALAR, ASESMEN, DAN REFLEKSI) MEMPERKOKOH PEMBELAJARAN BERMAKNA DAN PEMAHAMAN DIGITAL PENDIDIK - Nurlaila, Hanik (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This initiative is motivated by the challenges of implementing the Independent Curriculum in the digital era, where many teachers still struggle to shift from administrative lesson plan development to facilitating meaningful learning, resulting in a gap between policy and classroom practice. This best practice focuses on the implementation of the BINAR (Sharing, Innovation, Reasoning, Assessment, and Reflection) approach as a structured solution to strengthen educators' pedagogical competence and digital literacy. Key implementation steps include a series of integrated actions: building a culture of sharing good practices through learning communities; encouraging innovation through mentoring in the use of technology and AI; strengthening pedagogical reasoning through peer observation; developing authentic assessments; and cultivating continuous reflection. These actions were disseminated through intensive mentoring, workshops, and the initiation of the Inspirational Teacher Competition. Key findings indicate that the BINAR approach significantly enhanced teachers' creativity, digital literacy, and collaborative culture. Consequently, student motivation and engagement in meaningful learning increased, as reflected in the diverse range of creative projects produced. In conclusion, BINAR is an effective and applicable model for transforming teacher professionalism from the basic level, demonstrating that a cycle of sharing, innovation, and reflection is key to realizing relevant and meaningful learning. ABSTRAKDilatarbelakangi oleh tantangan implementasi Kurikulum Merdeka di era digital, di mana banyak guru masih kesulitan beralih dari penyusunan RPP administratif menuju fasilitasi pembelajaran yang bermakna, sehingga terjadi kesenjangan antara kebijakan dan praktik di kelas. Praktik baik ini berfokus pada penerapan pendekatan BINAR (Berbagi, Inovasi, Nalar, Asesmen, dan Refleksi) sebagai solusi terstruktur untuk memperkokoh kompetensi pedagogik dan pemahaman digital pendidik. Langkah-langkah penting implementasinya meliputi serangkaian aksi terpadu: membangun budaya berbagi praktik baik melalui komunitas belajar; mendorong inovasi dengan pendampingan penggunaan teknologi dan AI; menguatkan nalar pedagogis lewat observasi sejawat; mengembangkan asesmen autentik; serta membudayakan refleksi berkelanjutan. Aksi ini disebarluaskan melalui pendampingan intensif, lokakarya, dan inisiasi Lomba Guru Inspiratif. Temuan utama menunjukkan bahwa pendekatan BINAR berhasil meningkatkan kreativitas, literasi digital, dan budaya kolaborasi guru secara signifikan. Dampaknya, motivasi dan keterlibatan siswa dalam pembelajaran bermakna meningkat, yang tercermin dari beragamnya proyek kreatif yang dihasilkan. Kesimpulannya, BINAR merupakan model yang efektif dan aplikatif untuk mentransformasi profesionalisme guru dari tingkat dasar, membuktikan bahwa siklus berbagi, inovasi, dan refleksi adalah kunci untuk mewujudkan pembelajaran yang relevan dan bermakna.